To find the value of (-m)^-3n when m = 2 and n = -24, we substitute these values into the expression.
(-m)^-3n = (-2)^-3(-24)
Since (-2) raised to an even power is positive, and an odd power is negative, we can simplify (-2)^-3 as -1/(-2)^3.
(-1/(-2)^3)(-24) = (-1/(-8))(-24)
The negative signs cancel out, and we can multiply -1/(-8) and -24 to find the final result.
(-1/(-8))(-24) = (-1)(-3) = 3
Therefore, (-m)^-3n, when m = 2 and n = -24, is equal to 3.
What is (-m)^-3n if m=2 and n =-24
1 answer